Management of portal hypertension. Issue 949 (10th November 2004) - Samonakis, D N; Triantos, C K; Thalheimer, U; Patch, D W; Burroughs, A K
Abstract : Treatment of portal hypertension is evolving based on randomised controlled trials. In acute variceal bleeding, prophylactic antibiotics are mandatory, reducing mortality as well as preventing infections. Terlipressin or somatostatin combined with endoscopic ligation or sclerotherapy is the best strategy for control of bleeding but there is no added effect of vasoactive drugs on mortality. Non-selective β-blockers are the first choice therapy for both secondary and primary prevention; if contraindications or intolerance to β-blockers are present then band ligation should be used. Novel therapies target the increased intrahepatic resistance caused by microcirculatory intrahepatic deficiency of nitric oxide and contraction of activated intrahepatic stellate cells.